PENGEMBANGAN ALAT PERAGA SISTEM PEMILAH BIJI KOPI BERBASIS ARDUINO NANO UNTUK PEMBELAJARAN FISIKA AGRARIS - Ageng Sinta Pratiwi; M. Barkah Salim; Eko Prihandono (Universitas Muhammadiyah Metro, 2024)
Coffee is one of Indonesia's export commodities which has an important role ineconomic growth in Indonesia. Coffee production from 2020 to 2022 will experiencefluctuations. As for the causes of errors in post-harvest that are not appropriate to obtaingood quality coffee beans, post-harvest handling is needed by carrying out the sortingprocess, washing process, drying process and roasting process. The ADDIE method isused in developing this tool, including: Analysis stage, analyzing the need to develop aproduct and analyzing the feasibility and requirements for product development, Designstage, designing and designing a product. Development stage, development of productdesign. Implementation stage, realizing the design of a development product, testing theproduct developed in learning. Evaluation stage, evaluating the results of the productdeveloped and its application in the classroom. Validation data from three media expertson the props developed obtained an average percentage of 91.8%, meaning that they arevery suitable for use as props. And the validation results from three material experts on thetools and practice manual obtained an average percentage of 85.92%, which means it isvery suitable for use as a practice guide for teaching aids. Based on the average valuefrom the validation of media experts and material experts, the coffee bean sorting teachingaid shows that the criteria obtained are very feasible and the results of student responsesget a value with very practical criteria for use as a learning medium. The choice of materialsand design in making practical equipment has been taken into account, apart from usingmaterials that are not easily damaged, the shape is also made simple.